Effect of Exposure to Magnetic Field ELF (Extremely Low Frequency) 500Î¼T on pH and Physical Quality of Green Cayenne Pepper - Nuriyah, Sinta (Universitas PGRI Palembang, 2022)
Cayenne pepper (Capsicum frutescens L) is a horticultural crop commodity that has high economic value with fruit consisting of various combinations of colors and flavors. Extremely Low Frequency (ELF) magnetic fields are non-ionizing electromagnetic waves and have been widely used in various food fields. This study aims to examine the effect of exposure to the ELF magnetic field intensity 500 Î¼T Â for 60, 90, and 120 minutes on the pH and physical quality of green chili peppers. The research design used was Completely Randomized Design (CRD). The samples used were green chilies with 4 samples of the control group (without exposure to the ELF magnetic field) and 12 samples of the experimental group (the group that was exposed to the ELF magnetic field intensity of 500Î¼T). Measurements were made on days 2, 4, 6 and 8 after exposure. The results showed that the ELF magnetic field was able to inhibit the growth of lactic acid-forming spoilage microorganisms in chilies, thus affecting the pH and physical endurance indicators of green chili peppers. The effective dose in inhibiting the activity of lactic acid-forming bacteria in green cayenne pepper was exposure intensity of 500Î¼T for 120 minutes.Â Â